Ultrasound-guided tru-cut biopsy of abdominal and pelvic tumors in gynecology - Zikan, M; Fischerova, D; Pinkavova, I; Dundr, P; Cibula, D (Ultrasound in obstetrics & gynecology, 2010)
OBJECTIVE: To analyze the safety, adequacy and accuracy of tru-cut biopsy and to evaluate factors potentially affecting adequacy. METHODS: We analyzed retrospectively a group of patients who had undergone tru-cut biopsy for either primary suboptimally operable tumors, recurrence or suspected non-genital or secondary tumor. Tru-cut biopsy was performed either transvaginally or transabdominally, using an automatic biopsy gun with disposable needle and needle guide attached to the probe. The adequacy, i.e. obtaining a sample sufficient for identification of the origin of the tumor and performance of immunohistochemistry; accuracy, i.e. agreement between biopsy and final postoperative histology; and safety, as determined by complication rate, were assessed. Variables potentially influencing adequacy were analyzed using the orthogonal projections to latent structure method. RESULTS: A total of 195 biopsies were performed on 190 patients. An adequate sample was obtained in 178 (91.3%) biopsies. The final histology was not in agreement with the result from tru-cut biopsy in two out of 118 patients who underwent subsequent surgery (accuracy 98.3%). There were complications in two cases out of the 195 biopsies performed (1.0%). Ascites, elevated CA 125, primary suboptimal operable tumor, serous epithelial ovarian cancer histology, carcinomatosis and vaginal approach were significant positive predictors for the achievement of an adequate sample, while recurrence as an indication, non-serous and non-ovarian histotypes and transabdominal approach were negative predictors. CONCLUSION: Ultrasound-guided tru-cut biopsy is an efficient, minimally invasive, accurate and safe diagnostic method in the management of advanced, recurrent or atypical abdominal and pelvic tumors of probable non-genital origin, where unnecessary laparotomy or laparoscopy can be avoided. The adequacy of tru-cut biopsy is mainly influenced by indication group, histology, site of biopsy and approach. Our analysis can help in counseling the patient before the procedure and helps to explain the possible causes of failure of the procedure.
Keywords: Gynecology; lidé; Middle Aged; Adult; gynekologie; nádory pánve; intervenční ultrasonografie; Female; nádory břicha; Pelvic Neoplasms; retrospektivní studie; Biopsy; imunohistochemie; Humans; Immunohistochemistry; lidé středního věku; mladý dospělý; Ultrasonography, Interventional; biopsie; ženské pohlaví; Young Adult; Aged, 80 and over; senioři nad 80 let; Abdominal Neoplasms; Aged; Retrospective Studies; dospělí; senioři